Always courage / Yante Ismail - Ismail, Yante (Faculty of Art and Design, 2021)
Yante Ismail is a feminist artist. Her art challenges patriarchy, and the damaging social, religious, and cultural norms that dictate how women exist in society. She paints women who are bold, strong, and determined. She almost exclusively paints voluptuous female bodies in the nude to provide an alternative feminist narrative on the subject, reclaiming it from the ‘male gaze’ that defines the female body only as sexual or lewd or shameful or virginal. This piece was created in direct response to what I see in how the nation is feeling right now. Not the fear, not the anxiety, not the anger. But rising above all of that, against all odds, I see love, I see strength, and I see courage. Now more than ever, we need to see ourselves only as a nation of humans. And none of us is safe unless we are all safe. In our darkest hour, I believe we have the capacity to dig deep, and find the courage to hold on to our humanity. We will overcome.